Socio-cultural transformations of the family and behavior with respect to procreation - Donati, Pierpaolo (Medicina e Morale, 1993)
The Author examines the sociocultural transformations that the italian family has undergone over the last few years. These transformations have involved not only the structure of the family, but also the behaviour of the husband and wife with respect to procreation. The way one looks at a son has changed because by now he's a means to satisfy the needs of a couple which is more and more concentrated on itself and the search far its own realization. Thus the request for a son at any cost, even if this reduces the family, because of the intervention of external partners, to a simple means of catalogization, emptied of its deepest meanings. In the search for a way to overcome the present state, the Author indicates possible paths and also provides valid suggestions far more debates on the theme.